Design and Simulation Multichannel PWM Based on Modbus Protocol in FPGA Device - Kurniawan, Sigit; Idris, Mahmud; Sepdian, Sepdian; Mazwan, Mazwan (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2024)
Pulse Width Modulation (PWM) is a widely employed technique in power converter circuits. Given the prevalence of power converters in industrial settings, there is a need for a straightforward and efficient communication method among devices, such as the Modbus protocol. This study focuses on developing and simulating a multichannel PWM architecture integrated with Modbus modules. The objective is to create a multichannel PWM architecture with a Modbus module suitable for implementation on FPGA devices. The findings indicate that the architecture successfully facilitates the transmission and reception of Modbus frame data from the Modbus master. Data transmitted by the Modbus Master is utilized for reading or writing registers within the architecture, employing standard function codes such as 0x30, 0x04, 0x06, and 0x10. One of these functions serves to modify the duty value of the four PWM channels.